Deep insights into electrical parameters due to metal gate WFV for different gate oxide thickness in Si step FinFET. (3rd April 2019) - Saha, Rajesh; Bhowmick, Brinda; Baishya, Srimanta
Abstract : A systematic investigation of the impact of Ti metal gate work function variability (WFV) on various electrical parameters against variation in gate oxide thickness in both step‐FinFET and conventional FinFET (C‐FinFET) using technology computer‐aided design simulation is reported. It is seen that WFV of Ti metal gate has a significant influence on electrical parameters such as threshold voltage ( σV T ), subthreshold swing ( σ SS), on current ( σI on ), and off current ( σI off ) with variation in gate oxide thickness. It is also perceived that the impact of WFV of Ti gate material in step‐FinFET is lesser than C‐FinFET. Histograms of various electrical parameters are presented for better understanding of the statistical impact of WFV of Ti metal gate in both the structures.